Muse-Echo Blues de Xam Cartiér. El jazz como forma identitaria de estructuración del discurso novelesco (Altre Modernità, 2011)
By means of an analysis of sense structures in the novel Muse-Echo Blues by African-American writer Xam Cartiér, we make an interpretation of her approach to jazz techniques in creative writing which relates her intense work in surface-leveled prose with her regard to Negro woman identity issues.